2014
DOI: 10.1155/2014/398396
|View full text |Cite
|
Sign up to set email alerts
|

PEEK Cages versus PMMA Spacers in Anterior Cervical Discectomy: Comparison of Fusion, Subsidence, Sagittal Alignment, and Clinical Outcome with a Minimum 1-Year Follow-Up

Abstract: Purpose. To compare radiographic and clinical outcomes after anterior cervical discectomy in patients with cervical degenerative disc disease using PEEK cages or PMMA spacers with a minimum 1-year follow-up. Methods. Anterior cervical discectomy was performed in 107 patients in one or two levels using empty PEEK cages (51 levels), Sulcem PMMA spacers (49 levels) or Palacos PMMA spacers (41 levels) between January, 2005 and February, 2009. Bony fusion, subsidence, and sagittal alignment were retrospectively ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 43 publications
(104 reference statements)
1
28
0
Order By: Relevance
“…They found fusion was achieved in 93.5% of patients after a median follow-up of 23 months. In the other 12 articles, the analysis was performed by a clinician, usually a neuro-or orthopaedic surgeon [12,29,35,61,67,69,87,92,96,[109][110][111]. They found fusion was achieved in 85.5% of patients after a median follow-up of 23 months.…”
Section: Methods Of Measuring Bony Fusionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found fusion was achieved in 93.5% of patients after a median follow-up of 23 months. In the other 12 articles, the analysis was performed by a clinician, usually a neuro-or orthopaedic surgeon [12,29,35,61,67,69,87,92,96,[109][110][111]. They found fusion was achieved in 85.5% of patients after a median follow-up of 23 months.…”
Section: Methods Of Measuring Bony Fusionmentioning
confidence: 99%
“…Clinical outcome was assessed in relation to bony fusion in 18 studies ( Of these, 17 studies had a low risk of bias and 1 study had a high risk of bias. Out of these 18 studies, 3 found a statistically significant correlation between the occurrence of bony fusion and a good clinical outcome [109,120,122]. The other 15 studies did not find a correlation between bony fusion and clinical outcome.…”
Section: Correlation Between Bony Fusion and Clinical Outcomementioning
confidence: 97%
See 1 more Smart Citation
“…Because of the above-mentioned characteristics, in particular the good milling and grinding properties combined with high stability [6] similar to the stability of human bone [3], it is already used in various medical applications such as spine implant or bone substitute technology for large bone defects in traumatology [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Pseudo-arthrosis occurred in only two segments (3.3%). In comparison, Klingler et al, 17 reported ACDF in 51 levels using PEEK cages. Fusion occurred at (65%) after 20 months, while pseudo-arthrosis occurred in (35%).…”
Section: Discussionmentioning
confidence: 94%